Increasing Public Understanding Through Legal Socialization About Authentic Deeds - Alwi Jaya; Gustika Sandra; Tarmizi Tarmizi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Deed  is  something  matter  which is common found  in life public everyday. However unfortunately, society Still Not yet Lots know  about  deed, esp  to deed  authentic. Temporary there is a number of deed obeying the law regulation mandatory legislation made in form  deed  authentic. Based on to background behind the, Proposer in devotion to public  This  focused  to  enhancement  understanding public through  socialization  law about  deed  authentic carried out at the Suara Bone Beradat Legal Dialogue. However  because  situation  Covid- 19 pandemic, so  in carry out activity  devotion public This done  with teleconference method. From activities socialization law This expected public will obtain understanding about deed authentic, as well capable know difference between deed authentic with deed below hand along with with consequence their respective laws.